Traditional Exercises As a Practical Solution In Health Problems For Computer Users - Laurentius Noer Andoyo; Jozua Ferjanus Palandi; Zusana Pudyastuti (IC-ITECHS, 2014)
Of the total of 7.2 billion of world population, three billion of them are internet users. During 2013, the numbers of internet users in Indonesia have reached 74.75 million, including 31.7 million ‘Netizens’. The numbers of computer users are more than the number of internet users. These computer users are very susceptible to RSI (Repetitive Strain Injuries) which may be in the form of physical disorder, such as MSD (Musculoskeletal Disorders) or CVS (Computer Vision Syndromes), and various mental disorders. These disruptions are mainly due to people’s ignorance to ergonomic positions and incorrect attitude in using the computer for years. The biggest enemy of modern people is called ‘Disease of Civilization’, a disease caused by the changes in civilization due to the advancement of technology and bad life-style. Overcome the impact of modernization, people find the solution by “think backward” to old concept of the ancestors. Traditional exercise, which at first used for defense mechanism against the nature and enemies (animal and human), is now applied in the work life. Computer users can stay healthy by doing traditional exercises and self-massages. These two prevention efforts are cheap, practical, effective, and no big space required, yet they are very effective and powerful to maintain the health of computer users. In particular, the authors intend to invite computer users to cultivate “Safe and Healthy Computing’’ (‘‘Aman dan Sehat berKomputer’’ = ASK) by integrating exercises as a their life-style